Sosialisasi dan Pembuatan Paving Block dari Sampah Plastik di Desa Kadur - Fauzia Dwi Putri; Anggala Regina Br. T; Beby Adelia Hafiz Siregar; Dandi Darmawan; Dewi Lamsinar Simarmata; Amanda Riadi Lubis; Mahesti Fadilla; Nadia Ayshia Faiza; Nora Salsabilla; Tati Suranti (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Plastic waste is an environmental problem that is also experienced by the community of Kadur Village, Rupat Utara District, Bengkalis Regency. Based on field observations, plastic waste generated from household and community activities is still commonly burned, buried, or discarded without further utilization. This community service activity aimed to increase public knowledge and awareness of plastic waste management and to introduce practical skills for utilizing plastic waste as paving blocks. The target participants were the community of Kadur Village, including households, business actors, and other community members who generate or collect plastic waste. The activity was conducted through field observation, socialization, demonstration, direct practice, discussion, question-and-answer sessions, observation, and documentation. The results showed that the activity encouraged active community participation, particularly through questions, discussions, and involvement in the paving block production process. Participants gained new knowledge about plastic waste management and practical experience in transforming plastic waste into useful products. The activity also introduced an alternative approach to reducing plastic waste while opening opportunities for further environmental and economic development at the community level.